Regional analysis of the industrial development of Yakutia - Mikhail Yur'evich Prisyazhnyy (Экономика региона, 2011)
This paper highlights the most important and fundamental parts of the territorial analysis of the industrial mastering of Yakutia. Industrial mastering of the territory of Yakutia, which, to some extent, is the area of "new" mastering, flows typically for the northern regions and is characterized by significant region-to-region differences in the level of industrial mastering and the role of its individual branches. The leading industries in Yakutia are still extracting ones, which, specifying the first "layers" of mastering, have contributed to the rapid development of productive forces and the industrial mastering of the territory of republic. The republic has a distinct specialization in manufacturing of ore mining products. Industrial mastering is distinguished by lowest closeness of connection with the integral indicator of mastering, because it is the youngest, "pioneering" for the territory of republic. The paper assesses both level of mastering and level of stability of the existing mastering.